AUTOFLUORESCENCE BRONCHOSCOPY AS A MODALITY FOR EARLY DIAGNOSIS OF LUNG CANCER - KAW Nugraha; IDM Artika (Universitas Udayana, 2013)
Lung cancer has become a complicated health problem in the world. In 2005, approximately 172,500 people diagnosed with lung cancer in the United States. In Indonesia, lung cancer ranks fourth highest. Lung cancer is also the most common cause of death from cancer, so we need appropriate early detection modality to reduce the number of deaths from lung cancer. Compared with other modalities that currently available, Autofluorescence Bronchoscopy (AFB) seems to have better accuracy in early diagnosis of lung cancer. AFB can be used to evaluate patients with high-grade sputum atypia, evaluating patients with suspected or had suffered from lung cancer, and have a role in follow-up of bronchial high-grade intraepithelial neoplasia.